1987
DOI: 10.1093/rheumatology/26.3.193
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Antibodies to an Epstein-Barr Virus-Induced Polypeptide (Ebna-2) in the Sera of Rheumatoid Arthritic Families

Abstract: Using the protein immunoblot technique, antibodies to an Epstein-Barr virus-induced 92 kD polypeptide (EBNA-2) were more frequently present in the sera of patients with rheumatoid arthritis and their consanguineous relatives when compared with a control group. No association of anti-EBNA-2 antibody with the HLA-DR antigens was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…There have been many reports of high levels of EBV antibodies in RA patients (5)(6)(7)(8)(9)(10)(11). Our findings are consistent with those reports, and suggest that active EBV infection does exist in RA patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There have been many reports of high levels of EBV antibodies in RA patients (5)(6)(7)(8)(9)(10)(11). Our findings are consistent with those reports, and suggest that active EBV infection does exist in RA patients.…”
Section: Discussionsupporting
confidence: 92%
“…RA patients have a higher frequency and/or higher levels of serum antibodies against viral capsid antigen (VCA), early antigen (EA), and EBNA than normal individuals (5)(6)(7)(8)(9)(10)(11). It has been reported that the number of circulating B lymphocytes infected with EBV is increased in RA patients (12) and that EBV-specific T cell immunity is decreased (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Furthermore, our results show that elevated ELISA OD 450 readings of IgG antibodies to the EBNA-2(N) are associated with SLE, RA or SSc and with secondary SS. These results have extended early reports that described a high incidence of anti-EBNA-2 antibodies in rheumatoid sera [51].…”
Section: Discussionsupporting
confidence: 88%
“…The more frequent presence of antibodies to EBNA-2 in sera from RA patients than in healthy control sera [50,51] has been documented, but the characteristics and significance of the EBNA-2 antibodies are unknown. The elevated levels of EBNA-2 IgG may not be a cause, but a result, of its antigenic cross-reactivity with cellular or other proteins of infectious agents.…”
Section: Discussionmentioning
confidence: 99%
“…6). A similar heterogeneity in molecular weight has been reported previously for EBNA-2 [23,24]. In contrast, anti-MC antibodies reacted with the 70-75 kDa polypeptides present exclusively in the immunoprecipitates of anti-VCP2 antibodies (Fig.…”
Section: Anti-vcp2 Antibodies Immunoprecipitate Citrullinated Ebna-2supporting
confidence: 87%